SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN RUTE TERCEPAT KE LAUNDRY DI KUPANG DENGAN DIJKSTRA - Putra Prawira Yohanes Puka (Jurnal Publikasi Manajemen Informatika, 2026)
PUTRA PRAWIRA YOHANES PUKA. Decision Support System for Determining the Fastest Route in Kupang City from Home to Laundry Using the Dijkstra Method. Supervised by SKOLASTIKA SIBA IGON. This study aims to develop a Decision Support System (DSS) for determining the fastest route to laundry locations in Kupang City using Dijkstra's algorithm. The research was conducted from October to December 2024, utilizing digital map data from OpenStreetMap (OSM) and a dataset of laundry locations in the city. The system employs web-based technologies including XAMPP, Leaflet.js, and MySQL/MariaDB for database management. Data is processed by mapping locations as nodes and roads as edges with distance weights. The Dijkstra algorithm is applied to compute the shortest path, which is then displayed as an interactive map. The research includes system design phases such as database structuring, interface development, and algorithm implementation, followed by testing to ensure accuracy and functionality. The final result of this study is an interactive web-based system capable of calculating and displaying the fastest route to the nearest laundry location, providing both visual and textual navigation instructions using the Dijkstra algorithm, and offering a satisfactory user experience despite limitations in the completeness of manually defined node and edge data.